Identification of Nontuberculous Mycobacteria in Drinking Water in Cali, Colombia - Dávalos, Andrés F.; Garcia, Pamela K.; Montoya-Pachongo, Carolina; Rengifo, Andrea; Guerrero, Daniela; Díaz-Ordoñez, Lorena; Díaz, Gustavo; Ferro, Beatriz E. (International journal of environmental research and public health, 2021)
Nontuberculous mycobacteria (NTM) are ubiquitous microorganisms naturally resistant to antibiotics and disinfectants that can colonize drinking water supply systems. Information regarding the spread of NTM in specifically South America and Colombia is limited. We aimed to identify and characterize NTM present in tap water samples from Cali, Colombia. Drinking water samples and faucet biofilm swabs were collected in 18 places, including the city’s three main water treatment plants (WTPs). Filter-trapped material and eluates (0.45 μm) from swab washes were plated in 7H11 agar plates. Suspected colonies were evaluated microscopically, and NTM species were identified based on the rpoB gene. Antibiotic susceptibility testing was also performed. Fifty percent (9/18) of sampling points were positive for NTM (including two WTPs), from which 16 different isolates were identified: Mycobacterium mucogenicum (8/16), M. phocaicum (3/16), M. chelonae (2/16), M. mageritense (2/16), and M. fortuitum (1/16), all rapidly growing mycobacteria. A susceptibility profile was obtained from 68.75% (11/16) of the isolates. M. chelonae was the most resistant species. All NTM isolated are potentially responsible for human diseases; our findings might provide a baseline for exploring NTM transmission dynamics and clinical characterization, as well as potential associations between NTM species found in drinking water and isolates from patients.